Effect of low-density lipoprotein addition to soybean lecithin-based extenders on bull spermatozoa following freezing-thawing - preliminary results - Šimoník, O.; Rajmon, R.; Stádník, L.; Šichtař, J.; Beran, J.; Ducháček, J.; Hodek, P.; Trefil, P. (Czech Journal of Animal Science, 2016)
Soybean lecithin-based extenders represent an alternative to extenders containing egg yolk, but there has been discussion about their cryoprotective efficacy. Low-density lipoprotein (LDL) was proved as a cryoprotective agent, which can replace egg yolk in extenders. The aim of this study was to investigate the effects of LDL addition to the soybean extenders on their cryoprotective properties. The effect of the LDL of our production was verified using commercial egg yolk extender BULLXcell®, 6%, 8%, and 10% LDL (v/v) as an egg yolk replacement. The effects of LDL addition to the soybean lecithin-based extenders in concentrations of 4%, 6%, and 8% (v/v) were tested using extenders AndroMed® and Bioxcell®. In total, 64 samples from eight bulls were evaluated. Kinematic parameters of spermatozoa, resulting from Computer Assisted Sperm Analysis, and their viability, evaluated by fluorescent technique, were assessed immediately after thawing and after 2 hours. The quality of LDL compared to other studies was confirmed, and the beneficial effects of egg yolk replacement by LDL were proved in extender BULLXcell®. 8% LDL provided the best values for the majority of kinematic parameters (P < 0.05), without effect on total motility (P > 0.05). Furthermore, addition of 4%, 6%, and 8% LDL to the soybean lecithin-based extender Bioxcell® showed a positive effect on the majority of kinematic parameters of spermatozoa (P < 0.05) at both times of incubation. However there was no significant influence on total motility (P > 0.05). Viability was higher after thawing in the case of 8% LDL (P < 0.05). However, there was no consistent effect of LDL addition to the AndroMed® extender. In conclusion, cryoprotective properties of the semen extenders based on a soybean lecithin can be improved by the addition of LDL.
Keywords: bull sperm; cryopreservation; sperm motility; viability; cryoprotectant